We Hear-t You: a communication campaign cultivating confidence in parents to initiate mental health conversations with their youths - Ang, Jin Hui (Nanyang Technological University, 2023)
We Hear-t You is a communication campaign aimed at cultivating confidence in parents to initiate mental health conversations with their youth. Youths are the most susceptible to mental illness, yet among those who had experienced a mental disorder in their lifetime, a staggering 75% of them did not seek mental health treatment. Thus, this campaign targets parents with youths, aged 13-18, as the parental role has been identified as a crucial factor that influences youth mental health.